Comparison of damage mechanisms in curved composite laminates under static and fatigue loading. (1st April 2019) - Tasdemir, B.; Coker, D.
Abstract: In this paper, damage progression in curved CFRP composite laminates are experimentally investigated for static and fatigue loadings. Two different cross-ply laminate thicknesses are examined with grouped plies to elucidate the failure mechanisms. A test fixture is designed to apply moment/axial combined loading to curved specimens and DIC method is used to obtain the strain distribution in the curved region until failure. Our major finding is that under fatigue loading, the failure location and mechanism are different from that under static loading. Fatigue failure is observed to form where the radial stress is maximum whereas static failure is observed to form where the combined radial, tangential and shear stresses attain a maximum value, in the form of Tsai-Wu failure criterion. For fatigue failure, micro-cracks existing in the maximum radial stress location in the group of 90° layers grow under cyclic loading and coalesce into one major matrix crack which reaches the 0/90 interface gradually to continue as a delamination. On the other hand, static failure initiates inside the group of 90° layers with a dominant crack growing dynamically and jumps to the 0/90 interface near the arms with a 40–50° angle to continue as a delamination.